ANALISIS STRATEGI GURU DALAM MENINGKATKAN MINAT BACA SISWA PADA PEMBELAJARAN IPA - Sudarto Sudarto; Achamad Sabir; Nurfadilah Nurfadilah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aimsed to determine the strategies of teachers at SD Inpres 6/75 Biru which were carried out in increasing the students' reading interest in science learning as well as supporting and inhibiting factors in increasing the reading interest of High Grade students at SD Inpres 6/75 Biru. The research subjects were the teachers and the high grade students at SD Inpres 6/75 Biru, Tanete Riattang District, Bone Regency each in a ccount 3 people. Research data obtained through observation sheets and interviews. Data analysis techniques were data reduction, data presentation and conclusion drawing. Research results and conclusions: The strategy that’re used by SD Inpres 6/75 Biru teachers in increasing the students' reading interest in science learning, namely encouraging the students wanted to read books, preparing supporting facilities and infrastructure (for example, books that are interesting to students, namely the books that were consisted of picture), students are given a reading quiz with prizes for those who dared to appear in front of the class to read, and the formation of reading literacy groups in which the group was required to read for 15 minutes before class time. In implementing strategies to increase students' reading interest, the teacher got some support for learning in the classroom which could always be read at any time), there was a reading corner facility in each class, there was a seat in front of the class that could be used as a place to read, there was a comfortable atmosphere , as well as reading while gaming. Meanwhile, the inhibiting factors were the students got bored quickly and the students were not fluent in reading.